The Impact of Culture on the Strategy of Multinational Enterprises: Does National Origin Affect Ownership Decisions? - Hennart, Jean-françois; Larimo, Jorma (Journal of International Business Studies, 1998)
This paper tests the proposition that national origin affects the strategies of multinational enterprises by looking at the determinants of the choice they make between entering the United States through partially versus wholly owned subsidiaries. We pool entries into the United States made by firms based in two countries, Japan and Finland, which differ both in their cultural characteristics and in their cultural distance to the United States. After carefully controlling for the known firm and industry-level determinants of subsidiary ownership strategies, we find that cultural distance between the home base of the investor and the target country (or perhaps political risk) exerts a powerful influence on ownership of subsidiaries, but cultural characteristics of the home base do not.